Is Deliberation Equitable? Evidence from Transcripts of Village Meetings in South India - Ban, Radu (2012)
Deliberative decision-making processes are becoming increasingly important around the world to make important decisions about public and private goods allocation, but there is very little empirical evidence about how they actually work. In this paper the authors use data from India extracted from 131 transcripts of village meetings matched with data from household surveys conducted in the same villages prior to the meetings, to study whose preferences are reflected in the meetings. The meetings are constitutionally empowered to make decisions about public and private goods. The findings show that the more land a person owns, the higher the likelihood her preference is mentioned in the meeting, the longer the amount of time spent discussing this preference, and the higher the likelihood that a decision to provide or repair this public or private good is taken. At the same time, the voices of disadvantaged castes, while not dominating the meeting, are also heard. By contrast, the preferences of Muslims are given less time. High village literacy and the presence of higher level officials during village meetings mitigate the power of the landed, but political reservations for low castes for the post of village president increase the power of the landed.